If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(2x + 12) + 20 + -25 = 5(5x + -3) + 2 + -3 Reorder the terms: 9(12 + 2x) + 20 + -25 = 5(5x + -3) + 2 + -3 (12 * 9 + 2x * 9) + 20 + -25 = 5(5x + -3) + 2 + -3 (108 + 18x) + 20 + -25 = 5(5x + -3) + 2 + -3 Reorder the terms: 108 + 20 + -25 + 18x = 5(5x + -3) + 2 + -3 Combine like terms: 108 + 20 = 128 128 + -25 + 18x = 5(5x + -3) + 2 + -3 Combine like terms: 128 + -25 = 103 103 + 18x = 5(5x + -3) + 2 + -3 Reorder the terms: 103 + 18x = 5(-3 + 5x) + 2 + -3 103 + 18x = (-3 * 5 + 5x * 5) + 2 + -3 103 + 18x = (-15 + 25x) + 2 + -3 Reorder the terms: 103 + 18x = -15 + 2 + -3 + 25x Combine like terms: -15 + 2 = -13 103 + 18x = -13 + -3 + 25x Combine like terms: -13 + -3 = -16 103 + 18x = -16 + 25x Solving 103 + 18x = -16 + 25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25x' to each side of the equation. 103 + 18x + -25x = -16 + 25x + -25x Combine like terms: 18x + -25x = -7x 103 + -7x = -16 + 25x + -25x Combine like terms: 25x + -25x = 0 103 + -7x = -16 + 0 103 + -7x = -16 Add '-103' to each side of the equation. 103 + -103 + -7x = -16 + -103 Combine like terms: 103 + -103 = 0 0 + -7x = -16 + -103 -7x = -16 + -103 Combine like terms: -16 + -103 = -119 -7x = -119 Divide each side by '-7'. x = 17 Simplifying x = 17
| -2+2x=-3+13 | | 2p-2=8 | | 4y-7z=39 | | 6m+5=11 | | 300-10x=30x | | x^2*3x=3x^3 | | 4p+1=101 | | 0.16*((2.48-0.16*x)/0.2) | | [3x-2]=-16 | | 3o=9 | | -10(s+3)=-119 | | -12x-4=-x-81 | | 7(4s+9)=175 | | 3mx-1=m-3x | | 3cos(2x)+5sin(x)-4=0 | | 10=3-(x/10) | | 0=3-(x/10) | | 30=3-(x/10) | | -4-4X=-6+9X | | 300=3-(x/10) | | 19=17+2x | | 0=30-(x/10) | | x=30-(10/10) | | D^3-2D^2-3Dy=0 | | 18w+4= | | (3w+4)+(3w+4)= | | 4000/x=1.129 | | 3cos(2x)+5sin(x)=4 | | X-4/5=1/3 | | 15=60x-5y | | 2x/2-5=15 | | 1900/x=1.129 |